Human Resource Development Strategy At The Batangkaluku Agricultural Training Center In Gowa District - Tajuddin Tajuddin; Muh. Ikram Idrus; Edi Jusriadi (Green Publisher Indonesia, 2024)
Human resource development (HRD) in public organizations, including the Batangkaluku Agricultural Training Center, is crucial for achieving success and effectiveness. Technology, government policies, and other external dynamics are factors that influence HRD strategies. This research aims to identify alternative HRD strategies that are suitable for the organization's needs and potential. Through SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis and QSPM (Quantitative Strategic Planning Matrix), this research presents an overview of the organization's internal and external conditions as well as alternative strategies that can be adopted. The findings of this research contribute to the HRD literature and provide practical guidance for public organizations to formulate focused and relevant strategies. The conclusion of this research outlines the results of IFAS and EFAS, which yield several alternative strategies, such as developing the competence and excellence of the BBPP in agricultural workforce training, being responsive to the needs of the agricultural sector with training programs, actively promoting training programs and expanding partnership networks, and establishing a monitoring and evaluation system, with the third strategy showing the highest score in QSPM.